Identification Asthma Control Level And Its Factor Among Patient in A Tertiary Hospitals In Jakarta, Indonesia: A Cross-Sectional Study - Tuti Wiyati Wiyati; Rizqa Putri Hasanah (Pharmacy Department, Faculty of Health Sciences, UIN Syarif Hidayatullah Jakarta, Indonesia, 2025)
Poor asthma control level can result in mortality and morbidity in asthma patients. Therefore, it is important to detect it early and identify related factors. This was a cross-sectional study with data collection carried out in outpatient asthma patients in a tertiary hospital in Jakarta. The level of asthma control was measured using the Asthma Control TestTM (ACTTM) questionnaire. SPSS version 25 using Chi-Square Test was applied to determine risk factors that potentially associate with the level of asthma control. Forty-four patients met the criteria enrolled in this study. The results showed 43.2% of asthma patients were very uncontrolled, 27.4% of asthma patients were poorly controlled, and well-controlled asthma patients were 29.5%. There were not potential factor found to be associated with asthma control level of the patients.Keywords: Asthma, Asthma Control Level, Risk factors.